LHC signatures of scalar dark energy - Burrage, Clare; Brax, Philippe; Englert, Christoph; Spannowsky, Michael (American Physical Society, 2016)
Scalar dark energy fields that couple to the standard model can give rise to observable signatures at the LHC. In this work, we show that tt¯+missing energy and monojet searches are suitable probes in the limit where the dark energy scalar is stable on collider distances. We discuss the prospects of distinguishing the dark energy character of new physics signals from dark matter signatures and the possibility of probing the self-interactions of the dark energy sector.